MANAGEMENT OF HATCHERY PRODUCTION VANAME (Litopenaeus vannamei) NAUPLI IN INSTALLATION OF SHRIMP (IPU) GELUNG BRACKISH WATER AQUACULTURE CENTRE (BPBAP) SITUBONDO EAST JAVA - Choirul Anam; Ach. Khumaidi; Abdul Muqsith (Faculty of Science and Technology University Ibrahimy, 2016)
Vaname (Litopenaeus vannamei) is a commodity brackish water, which has been much in demand and become a superior product aquaculture sector in Indonesia. This is because some of the advantages possessed by vaname prawns, which are can be maintained with high stocking density, rapid growth, has a high resistance to disease and environmental change. In its natural habitat, the shrimp vaname usually make the process of mating at night time, but the most active usually occurs at sunset. The mating process occurs in four stages, namely the approach, chase, perangkakan and mating. This process can be seen by looking at the behavior of the male parent who swim with the female parent. Both of these stem looks like a chase. Then swim parallel to the male parent and a female parent turned toward ventral female shrimp. After that the male parent and a female parent gripping releasing sperm attached to thellycum. In the larval rearing, which must be considered is the management of water quality and feeding management. This is because water is a live media aquatic organism that is crucial to the survival rite larvae. Besides feeding management also determine the success or failure of an aquaculture business where feed costs reached 60-75% of total production costs.